2017
DOI: 10.24099/vet.arhiv.160117
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial and antioxidant properties of Elettaria cardamomum Maton extract and its effects, incorporated with chitosan, on storage time of lamb meat

Abstract: ________________________________________________________________________________________ SHARAFATI-CHALESHTORI, F., R. SHARAFATI-CHALESHTORI:In vitro antibacterial and antioxidant properties of Elettaria cardamomum Maton extract and its effects, incorporated with chitosan, on storage time of lamb meat. Vet. arhiv 87, 301-315, 2017. ABSTRACTIn this experimental study, ethanolic extract of Elettaria cardamomum Maton (ECM) was prepared, the amount of phenolic compounds and antioxidant properties were measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Previous works have demonstrated the antioxidant activity and antibacterial properties of essential oils and extracts. 2 , 23 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works have demonstrated the antioxidant activity and antibacterial properties of essential oils and extracts. 2 , 23 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Previous works have demonstrated the antioxidant activity and antibacterial properties of essential oils and extracts. 2,23,25,26 Abbreviations: E, ethanolic extract; EO, essential oil; NE, no effect. Our results showed that B persicum, E globulus, and rose water had antioxidant activities (Figure 1), which was supported by previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of active compounds present in such residues may well be through their incorporation in diverse biodegradable and edible matrices as, among others, galactomannan, sodium alginate or particularly chitosan (Costa, Maciel, Teixeira, Vicente, & Cerqueira, 2018), which has demonstrated good preservative capacities on sheep's (Cerqueira et al, 2009) and goat's (Cano-Embuena et al, 2017) cheeses. Furthermore, chitosan has previously demonstrated capacities as carrier for the incorporation of different vegetal extracts (Bonilla & Sobral, 2016;Kalaycıoğlu, Torlak, Akın-Evingür, Özen, & Erim, 2017;Shahbazi, 2017;Sharafati-Chaleshtori & Sharafati-Chaleshtori, 2017;Siripatrawan & Harte, 2010) and incorporated as GRAS (Generally Recognized as Safe) by the Food and Drug Administration (FDA, 2002) and in the Union list of novel foods under the Regulation (EU) No 2017/2470 of 20 December 2017.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the highest inhibitory activity was observed against S. typhi (26) . Sharafati et al (2017) reported that the green cardamom ethanolic extract had an antibacterial effect against Enterobacteriaceae (27) . Naeini et al (2011) examined the antifungal effects of 50 herbal medicines using the disk diffusion method.…”
Section: Discussionmentioning
confidence: 99%